Assembleia-Geral de Credores na recuperação judicial - Mange, Eduardo Foz (2010)
This study analyzes the General Assembly of Creditors, in the process of Judicial Reorganization under Law 11.101/2005. The thesis to be examine is whether the General Assembly fulfills the function idealized by the legislature which is to transfer the decision on the continuation of business activity or the declaration of bankruptcy to the creditors of the society in economic and financial crisis. To verify this issue the author undertook a study of the legislative history of Brazilian Law, made a comparative law analysis and verify the interpretation of current Brazilian Law in case law and by respected commentators. The most controversial points (or issues) on the subject were analyzed under legislation, doctrine and case law. The author points out what can be improved and developed either by the legislature or by the interpreter of the standard. Despite some points displayed throughout this study can be improved, the conclusion is that in most of the cases the General Assembly of Creditors has fulfilled the function targeted by the legislature. Thus, in most cases the lenders have the power to decide on the continuation of business activity or declaration of bankruptcy